Lateral migration resistance of screw is essential in evaluating bone screw stability of plate fixation - Xiaoreng Feng (Nature Portfolio, 2021)
Abstract Conventional evaluation of the stability of bone screws focuses on pullout strength, while neglecting lateral migration resistance. We measured pullout strength and lateral migration resistance of bone screws and determined how these characteristics relate to screw stability of locking plate (LP) and dynamic compression plate (DCP) fixation. Pullout strength and lateral migration resistance of individual bone screws with buttress, square, and triangular thread designs were evaluated in polyurethane foam blocks. The screw types with superior performance in each of these characteristics were selected. LP and DCP fixations were constructed using the selected screws and tested under cyclic craniocaudal and torsional loadings. Subsequently, the association between individual screws’ biomechanical characteristics and fixation stability when applied to plates was established. Screws with triangular threads had superior pullout strength, while screws with square threads demonstrated the highest lateral migration resistance; they were selected for LP and DCP fixations. LPs with square-threaded screws required a larger force and more cycles to trigger the same amount of displacement under both craniocaudal and torsional loadings. Screws with triangular and square threads showed no difference in DCP fixation stability under craniocaudal loading. However, under torsional loading, DCP fixation with triangular-threaded screws demonstrated superior fixation stability. Lateral migration resistance is the primary contributor to locking screw fixation stability when applied to an LP in resisting both craniocaudal and torsional loading. For compression screws applied to a DCP, lateral migration resistance and pullout strength work together to resist craniocaudal loading, while pullout strength is the primary contributor to the ability to resist torsional loading.